Implementasi Metode Demonstrasi Pada Pembelajaran Fiqih dalam Mengatasi Kejenuhan Belajar Siswa Kela VII A di SMP Darul Hikmah Langkap Burneh Bangkalan - Syamsul Maarif, Mohammad (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2025)
This study aims to overcome the learning boredom of class VIIA students at SMP Darul Hikmah Langkap Burneh Bangkalan. The research method used is Classroom Action Research (CAR), focusing on student learning outcomes and problematic services in the learning process. The subjects of the study were 31 class VIIA students. The results of the study showed that there was a significant increase in student enthusiasm for the fiqh learning material provided and students' positive responses to the demonstration method. This increase can be seen from the percentage of students who chose strongly agree (SS) in cycles I and II. Student responses to Fiqh learning with the demonstration method were categorized as good. In addition, the results of the increase in scores given by observers also showed an increase in learning management using the demonstration method. The observer's assessment score increased from cycle I to cycle II. Based on these findings, it can be concluded that the implementation of the demonstration method is effective in overcoming the learning boredom of class VIIA students at SMP Darul Hikmah Langkap Burneh Bangkalan.